Representations of Classical Greece in Theme Parks - Carlà-Uhink, Filippo (IMAGINES - Classical Receptions in the Visual and Performing Arts Ser, 2020)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Contents -- Figures -- Acknowledgements -- 1 Representing History in the Theme Park: The Case of Ancient Greece -- 'It's a Small World' after all - and it includes Greece -- Historical theme parks and their uses of the past -- Theme parks, representations of the past and historical culture -- Postmodern aesthetics and the (ancient) past: Affective turn and pastness -- Ancient Greece in reception -- Ancient Greece in the theme park -- 2 German Philhellenism in the Theme Park -- The position of ancient Greece in German culture -- 'Griechenland', Europa-Park, Rust -- 'Strand der Götter', Belantis, Leipzig -- 3 Spain, Ancient Greece and the Land of Myths -- Ancient Greece in Spanish popular culture -- Terra Mítica, Benidorm -- 4 Ancient Greece, the United States of America and the Theme Park -- The presence of ancient Greece in US American (popular) culture -- Glimpses of ancient Greece in US parks -- Mt. Olympus, Wisconsin Dells, Wisconsin -- 5 The Far East, Ancient Greece and the Theme Park -- Ancient Greece in Eastern Asia -- Happy Valley Beijing, People's Republic of China -- E-Da, Kaohsiung, Republic of China -- 6 Ancient Greece in France: The World of a Gallic Warrior -- Re-mediatization and the theme park -- Ancient Greece in France -- Ancient Greece in the Astérix world -- Parc Astérix -- 7 Greece - In the Form of a Conclusion -- Notes -- Bibliography -- Index.